1997
DOI: 10.1037/0021-9010.82.5.656
|View full text |Cite
|
Sign up to set email alerts
|

The effects of varying conceptualizations of job performance on adverse impact, minority hiring, and predicted performance.

Abstract: The present research explored the effects of various strategies of weighting criterion dimensions on adverse impact, minority hiring, and job performance. In particular, this research compared strategies that vary the weight of task and contextual performance dimensions in calculating a composite criterion measure, in terms of their effects on regression weights assigned to predictors and effects on adverse impact, percentage of minorities hired, and predicted performance. With a Monte Carlo simulation based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 34 publications
3
85
0
Order By: Relevance
“…The standard deviations of the input parameter distributions (cf. the values reported between brackets in Table 1) are based on results presented by Bobko et al (1999); Hattrup, Rock, and Scalia (1997); Hough et al (2001); Hunter and Hunter (1984);…”
Section: Illustrationmentioning
confidence: 99%
“…The standard deviations of the input parameter distributions (cf. the values reported between brackets in Table 1) are based on results presented by Bobko et al (1999); Hattrup, Rock, and Scalia (1997); Hough et al (2001); Hunter and Hunter (1984);…”
Section: Illustrationmentioning
confidence: 99%
“…Ethnic score differences between .50 SD and 1.50 SD on cognitive ability tests have often been found (e.g., Herrnstein & Murray, 1994). However, evidence has been found that ethnic differences in cognitive ability test scores are considerably larger than ethnic differences in measures of job performance (Hattrup, Rock, & Scalia, 1997;Waldman & Avolio, 1991).…”
Section: Objective Measures Cognitive Ability Testsmentioning
confidence: 99%
“…impact (Hattrup, Rock, & Scalia, 1997;Sackett & Ellingson, 1997). Weighting task performance less than contextual performance in the overall performance measure will make cognitive ability less important in hiring and will lead to less adverse impact (Hattrup et al, 1997).…”
Section: Applicants Will Infer Job and Organizational Information Basedmentioning
confidence: 99%